2012
DOI: 10.1177/0194599812458087
|View full text |Cite
|
Sign up to set email alerts
|

Pneumolabyrinth following Eustachian Tube Insufflation

Abstract: P neumolabyrinth is a condition in which the vestibule and/or cochlea is filled with air. 1 Eustachian tube insufflation (ETI) is a type of treatment for recurrent serous otitis media that is still popular in Europe. It exploits the anti-inflammatory and mucolytic effects of thermal waters containing sulfur and bromo-iodine gas.To our knowledge, no case of a pneumolabyrinth due to barotrauma provoked by ETI has been described previously. The aim of this article is to present a patient who developed a pneumolab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Impaired Eustachian tube function is often referred to as Eustachian tube dysfunction. Clinical manifestations of ETD are aural fullness, otalgia and/or hearing loss or could be a “latent” condition ( 54 56 ). Magliulo et al ( 57 ) assessed that In patients with obstructive sleep apnea syndrome, several factors (nasal obstruction, increase in upstream airflow resistance, inflammation of the rhinopharynx and the Eustachian tube (ET) orifice mucous) could be responsible for ET collapse, hindering its correct opening to exchange air with the middle ear.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired Eustachian tube function is often referred to as Eustachian tube dysfunction. Clinical manifestations of ETD are aural fullness, otalgia and/or hearing loss or could be a “latent” condition ( 54 56 ). Magliulo et al ( 57 ) assessed that In patients with obstructive sleep apnea syndrome, several factors (nasal obstruction, increase in upstream airflow resistance, inflammation of the rhinopharynx and the Eustachian tube (ET) orifice mucous) could be responsible for ET collapse, hindering its correct opening to exchange air with the middle ear.…”
Section: Discussionmentioning
confidence: 99%
“…Magliulo et al recently reported an interesting case of “pneumolabyrinth following Eustachian tube insufflation” in Otolaryngology–Head and Neck Surgery. 1 Pneumolabyrinth, as it has been described in the article, is a condition of vestibule and/or cochlea dysfunction due to the presence of air within the labyrinth. It is caused by a perilymphatic fistula that can be the result of temporal bone trauma, barometric pressure changes, or otologic surgery.…”
mentioning
confidence: 98%